More housing - Unknown (Tufts Archival Research Center, 2018)
Depicts a raised fist emerging out of urban homes and buildings. The text reads: "More / Housing / ? / Tax / the / Slumlords". The bottom right hand corner of the poster reads "ABCTU". This is the only poster in the folder.